Perception of Public Relations Officers on Government Public Relations Approaches Towards the Acceptability of COVID 19 Vaccination in Taraba State Nigeria - Faith, Bamigboye Damilola (Darul Yasin Al Sys, 2024)
This study on Perception of Public Relations Officers on Government Public Relations Approaches towards the Acceptability of Covid 19 Vaccination in Taraba State, Nigeria sought to determine the level of awareness of public relations approaches used by the government in the campaign for the Covid-19 vaccine acceptance, determine how public relations experts perceive the impact of government public relations approaches in the Covid-19 vaccine campaign, identify the specific challenges faced by public relations experts in the campaign for Covid-19 vaccine and identify public relations strategies that can enhance public trust and engagement in the Covid-19 vaccine campaign in Taraba State. The study employed the survey method of research design with a population of 158. Using purposive sampling method, questionnaire was administered on a sample size of 103 respondents within the study area to elicit primary data. Findings of the study revealed that respondent perceived different public relations approachs used by government isn the campaign for Covid-19 vaccination acceptance in Taraba State such as information about the disease and the vaccine through mass media, using traditional communication, sponsorship of some programmes/events among others in the campaign for the Covid-19 acceptance respectively. The study also found that the public relations approaches by government to ensure that Covid-19 vaccination was accepted by people did not impact meaningfully on the people as they were perceived not to have agreed to come out and take the vaccination. The study concluded that the government's adoption of diverse PR strategies, including communication campaigns, media relations efforts, and collaboration with healthcare providers did not improve Covid-19 vaccine acceptance amidst hesitancy and other challenges. Finally, the study recommended among others community engagement through grassroots initiatives, involving local influencers, community leaders and healthcare providers as a way of reducing hesitancy to Covid-19 vaccine among people in Taraba State and Nigeria as a whole.